2016
DOI: 10.1136/annrheumdis-2016-eular.3162
|View full text |Cite
|
Sign up to set email alerts
|

AB0032 The Adenosine Deaminase Isoforms Activity in Synovial Fluid in Patients with Different Arthritis

Abstract: BackgroundArthritis is one of the most common causes of people's disability in the world. Recent years investigations were done to find biomarkers which can help in differentiating the type of arthritis, to evaluate the correlation between marker and disease severity. A purine nucleoside adenosine possesses anti-inflammatory activity via decreasing the level of pro-inflammatory cytokines, increasing the level of anti-inflammatory cytokines and represents one of the potent regulators of the inflammatory respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Specifically, in rheumatoid arthritis (RA) patients, the levels of cfDNA in synovial fluid (SF) and peripheral blood were highly elevated [ 4 ]. Genetic sequencing also identified that cfDNA in SF of RA was rich in hypomethylated cytosine-phosphate- guanosine (CpG) and could cause severe inflammation both in vitro and in vivo through upregulation of TNF-α expression [ 5 , 6 ]. Therefore, cfDNA is crucial for RA process.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in rheumatoid arthritis (RA) patients, the levels of cfDNA in synovial fluid (SF) and peripheral blood were highly elevated [ 4 ]. Genetic sequencing also identified that cfDNA in SF of RA was rich in hypomethylated cytosine-phosphate- guanosine (CpG) and could cause severe inflammation both in vitro and in vivo through upregulation of TNF-α expression [ 5 , 6 ]. Therefore, cfDNA is crucial for RA process.…”
Section: Introductionmentioning
confidence: 99%
“…Its large extracellular form (LADA, Mm ≥ 260 kDa) is a non-covalent complex of SADA with dipeptidyl peptidase 4 enzyme (DPP4). The described in our works accumulation of SADA in synovial fluids at RA was a consequence of autoimmune nature of this pathology [20], when SADA citrullination prevented its interaction with DPP4 and transformation into LADA [21,22]. At T2DM, the observed increase of ADA activity in blood plasma, can lead to changes in immunity and exacerbation of the pathogenesis [23,24].…”
mentioning
confidence: 86%